THE EFFECT OF INDIVIDUAL LEARNING ON STUDENTS’ SPEAKING ABILITY - Ishak Ishak; Euis Yanah Mulyanah (Jurnal Dinamika UMT, 2017)
The objectives of the research are to improve students’ speaking and to enrich the effective techniques for the students in improving their speaking ability. This is an experimental study conducted at SMA AL-Husna Tangerang. The researcher collects the data from 40 students as sample from 12th Grade SMA Al-Husna  Tangerang in academic year 2015/2016 spread in two classes, one class as the experiment group another one is the control group. The researcher used a true experimental research design to get the data and the data are gathered through pretest and posttest of speaking by using interesting short stories as the instrument of the research. The result of the research shows that the mean of gained score is 1.9. It can be concluded that the result of the posttest (after having treatment) greater than pretest. The research hypothesis accepted and null hypothesis is rejected. It means there is significant difference of teaching students’ speaking ability both classes. Based on the result of t-test shows that tobserved (8,07) > (1.73) ttable. So, Ho is rejected and Ha is accepted. It means teaching speaking using Individual learning technique is effective in improving students’ speaking ability.   Keywords: Individual learning, Speaking ability